2017
DOI: 10.1038/s41598-017-09349-0
|View full text |Cite
|
Sign up to set email alerts
|

Src-dependent EGFR transactivation regulates lung inflammation via downstream signaling involving ERK1/2, PI3Kδ/Akt and NFκB induction in a murine asthma model

Abstract: The molecular mechanisms underlying asthma pathogenesis are poorly characterized. In this study, we investigated (1) whether Src mediates epidermal growth factor receptor (EGFR) transactivation; (2) if ERK1/2, PI3Kδ/Akt and NF-κB are signaling effectors downstream of Src/EGFR activation; and (3) if upstream inhibition of Src/EGFR is more effective in downregulating the allergic inflammation than selective inhibition of downstream signaling pathways. Allergic inflammation resulted in increased phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 56 publications
4
74
0
Order By: Relevance
“…Arrows point to the regions of interest referred to in the Results sections airways inflammation. 55 Our novel finding that ERBB3 is up-regulated in severe asthma requires further investigation as it suggests that EGFR/ ERBB3 heterodimers may contribute to corticosteroid-refractory asthma. As EGFR and corticosteroids also have beneficial effects on epithelial repair and barrier function, 54 discriminating between pro-inflammatory and pro-repair functions for these pathways, and the role(s) of individual ligands and ERBB receptor heterodimers, should help to tailor more effective therapies for severe asthma.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Arrows point to the regions of interest referred to in the Results sections airways inflammation. 55 Our novel finding that ERBB3 is up-regulated in severe asthma requires further investigation as it suggests that EGFR/ ERBB3 heterodimers may contribute to corticosteroid-refractory asthma. As EGFR and corticosteroids also have beneficial effects on epithelial repair and barrier function, 54 discriminating between pro-inflammatory and pro-repair functions for these pathways, and the role(s) of individual ligands and ERBB receptor heterodimers, should help to tailor more effective therapies for severe asthma.…”
Section: Discussionmentioning
confidence: 92%
“…53 We have previously shown that EGFR protein expression is increased in the bronchial epithelium of asthmatic patients according to disease severity 54 ; furthermore, EGFR expression correlates with epithelial IL-8 levels and the extent of neutrophilic inflammation in severe asthma. 33,34 Although involvement of the EGFR in inflammatory responses has been demonstrated previously using murine models of ovalbumin 55 or house dust mite-induced allergic inflammation, 56,57 both of these models are corticosteroid sensitive and so cannot address those corticosteroid-refractory responses that are important in severe asthma. Using the IL-13 transgenic mouse model, we identified a subset of IL-13-driven F I G U R E 4 The Type 2 lung inflammation signature is reduced by dexamethasone, but not the proneutrophilic responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, EGFR is a surface protein that binds to the epidermal growth factor and is expressed in many cell types of the lungs, including smooth muscle cells, endothelial cells, broblasts, and epithelial cells [63]. Its immunoreactivity induces the production of mucin in the airway and airway remodeling [64] and triggers airway in ammation by activating intracellular signaling pathways [65]. Signal transducer and activator of transcription-3 (STAT-3) plays an important role in the development and maturation of tissue functions in vertebrates, including in ammation control and immunity [66].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is an epidermal growth factor receptor that is widely distributed in epithelial tissues and plays an important regulatory role in the development of respiratory in ammation [20,21,22]. EGFR inhibitors can effectively inhibit acute in ammation of the rat respiratory tract caused by exogenous zinc ions [23].…”
Section: Discussionmentioning
confidence: 99%